Performance Analysis of Synchronous Generators at Kamojang Geothermal Power Plant Unit 5 Based on Operational Parameters of Power, Current, and Voltage - Alamsyah, Amanda Putri; Sucita, Tasma; Mulyana, Elih (Journal La Multiapp, 2025)
Geothermal energy is one of the potential and sustainable renewable energy sources in Indonesia. The efficiency of the generation system is one of the crucial aspects in optimizing the utilization of this energy. This study aims to analyze the performance of synchronous generators at the Kamojang Unit 5 Geothermal Power Plant based on power, current, and voltage parameters. The method used is a quantitative descriptive approach with field data collection for seven consecutive days in January 2025. The data observed include active power, apparent power, power factor, terminal voltage, phase current, and generator efficiency and current imbalance between phases. The results showed that the generator had high and stable daily efficiency with an average of 93.99%. The power factor was also classified as good, with an average of 91.23%. The highest phase current imbalance occurred in phase V with an average of 1.60%, but was still within the safe threshold according to IEEE standards. These findings indicate that the generation system at the Kamojang Unit 5 Geothermal Power Plant operates in an efficient and stable condition. This study also indicates the importance of monitoring operational parameters periodically as part of a maintenance strategy and increasing the reliability of geothermal power plants. With high efficiency and system stability, Kamojang Unit 5 Geothermal Power Plant can be a model for reliable and sustainable renewable energy power plant operation.